Design and development of electrical system on hydrokinetic turbines for home power - Hazirah, Roslan (2018)
Nowadays, there are many types of turbines that can found. However, most of them were applied on dam that need high water flow rates. However, in this project low water flow rates of Hydrokinetic Turbine will be use. Therefore, improvement of this mechanisme will apply in rural area. From improving Hydrokinetic Turbines this mechanisme will produce electricity to supply to rural area. Therefore, this project is proposed the application of the Hydrokinetic Turbine which is Cross-flow Water Turbine. This project is focused on small river which the water flow rates is low and suit to Cross-flow Water Turbine where the velocity and pressure is to be determined with the reading of Cross-flow Water Turbine will read by software NX 10 Nastran: Siemens PLM Software. At the end of this project, a several testing has been done to prove that an electricity produced by the turbines is sufficient to provide enough low consumption appliances.